Characterizations of base and subbase layers for Mechanistic-Empirical Pavement Design. (15th October 2017) - Su, Ningyi; Xiao, Feipeng; Wang, Jingang; Amirkhanian, Serji
Highlights: Various base and subbase layers of highway pavement were influenced by numerous factors. Typical layers are unbound aggregate, asphalt and cement treated, permeable, and recycled. Influence factors include resilient modulus, materials, thickness, gradation, and moisture content. Performances are sensitive to changes of resilient modulus, moisture content, temperature, and load levels. Abstract: The main feature of Mechanistic-Empirical Pavement Design Guide (MEPDG) versus AASHTO 1993 is the various variables as inputs including the material properties, traffic load and climate. Currently, the influences of material type and the thickness of surface layer on pavement performance have generated many interests but the importance of base and subbase layers for predicting the pavement performances is not paid enough attention. Therefore, this review explores the influences of different factors on pavement performances when various types of base courses are employed in pavement structure including unbound aggregate base layer, asphalt treated base layer, cement treated base layer, permeable base layer, and the recycled pavement base layer. And the influence factors of base layer on pavement performances include the resilient modulus, material type, thickness of base, gradation of aggregate, moisture content, and the property of subbase layer, which are divided into internal and external causes. In addition, the parameters of subbases layer are also regarded as individual factors to analyze the influence on pavement performance. The pavement performances are more sensitive to the change of resilient modulus, moisture content, temperature, and load levels, but they are not sensitive to the thickness of subbase layer and the Poisson's ratio of materials. In addition, temperature cycling per day is the major reason for resulting in reflective cracks for chemical stabilized base pavement.